A subgradient extragradient algorithm with inertial effects for solving strongly pseudomonotone variational inequalities. (1st September 2020) - Fan, Jingjing; Liu, Liya; Qin, Xiaolong
ABSTRACT: In this paper, we introduce a new algorithm by incorporating inertial terms in a subgradient extragradient algorithm for solving variational inequality problems involving strongly pseudomonotone and Lipschitz continuous operators in Hilbert spaces. The strong convergence of the algorithm is obtained under mild assumptions. We also provide some numerical examples to illustrate that the acceleration of our algorithm is effective.